Balloon-assisted Transcatheter arterial embolization using N-butyl cyanoacrylate for iatrogenic arterial bleeding by groin puncture: a new technology - Ueda, Tatsuo (CVIR Endovasc, 2020)
BACKGROUND: Balloon-assisted transcatheter arterial embolization (TAE) using n-butyl cyanoacrylate (NBCA) and lipiodol (Lp) mixture is a new endovascular treatment technique for iatrogenic arterial bleeding by groin puncture. It is less invasive compared to surgical repair, and NBCA migration into the circulation can be prevented by temporary balloon occlusion of the parent artery without ultrasound-guidance. This study aimed to report on the technical aspects and evaluate the efficacy and safety of fluoroscopically guided balloon-assisted transcatheter arterial embolization using NBCA for iatrogenic arterial bleeding by groin puncture. MATERIALS AND METHODS: The study included five patients (mean age 54.6 years; 3 male and 2 female) with iatrogenic arterial bleeding by groin puncture. We performed transcatheter arterial embolization using NBCA while occluding the responsible artery with a balloon catheter during the embolization to prevent NBCA migration. Two sheaths were inserted into the common femoral artery. A microcatheter was advanced into the pseudoaneurysm or extravasation via the contralateral sheath. A balloon catheter was advanced into the responsible artery until the balloon portion covered the leakage site via another sheath. After balloon inflation, the NBCA and Lip mixture was slowly injected until the pseudoaneurysm, or the extravasation was filled without touching the balloon. The microcatheter was removed immediately after the filling. We assessed technical success, overall success, and complications. RESULTS: The injured arteries were the external iliac artery (n = 1), the common femoral artery (n = 2), and the proximal portion of the superficial femoral artery (n = 2). NBCA was injected once in four cases and twice in one case where complete hemostasis could not be achieved with one injection. The technical and overall success rate was 100% with no complications, including distal embolization of NBCA. CONCLUSIONS: Balloon-assisted TAE using NBCA is a feasible, effective, and safe treatment for iatrogenic arterial bleeding by groin puncture. It may also be applicable in other arterial bleeding situations where the potential risk of distal embolization can be decreased by applying the balloon-assisted technique.